PENCIPTAAN MANUSIA DALAM AL-QUR'AN: Sebuah Pendekatan Ekofeminis - Roma Wijaya (STAI AL-ANWAR SARANG, 2025)
This study examines the interpretation of gender-related verses in the Qur'an through an ecofeminist framework. The primary focus is on Q.S. An-Nisa' (4):1, which has traditionally been interpreted by classical commentators in ways that reinforce patriarchal culture, often labeling women as the